The Alcohol and Epoxy Alcohol of Zingiberene, Produced in Trichomes of Wild Tomato, Are More Repellent to Spider Mites Than Zingiberene - Dawood, Mohammad H.; Snyder, John C. (Frontiers in Plant Science, 2020)
Allelochemicals that are present in trichome secretions of wild tomato species play a major role in mediating interactions with arthropods, often conferring high level of resistance via antibiosis and antixenosis. Plant breeders are attempting to exploit wild relatives of tomato with the aim of creating insect-resistant plants. Tomato is grown world-wide and is one of the most economically important vegetables. Nevertheless, tomato is a host for numerous pests that can reduce productivity. Tomato breeders have focused more on increasing fruit quantity and quality and less on enhancing crop resistance to herbivores. Many accessions of the wild tomato relative, Solanum habrochaites (S.h), possess high levels of resistance to arthropods. The monocyclic sesquiterpene hydrocarbon, 7-epi-zingiberene, is a major defensive component found in trichome secretions of certain accessions of S.h. We have used LA2329, an S.h. accession, as a donor in a breeding program designed to introgress zingiberene into cultivated tomato. However, the composition of trichome secretions in our population of LA2329 is segregating, with some individuals producing mainly 7-epi-zingiberene in their secretions while others producing two additional, unidentified compounds in their trichome secretions. To investigate if these other compounds may also contribute to arthropod resistance, trichome secretions were collected from plants of S.h LA2329 grown under greenhouse conditions and then major compounds were isolated by silica gel column chromatography and tested for their ability to repel two spotted-spider mite (TSSM), Tetranychus urticae. Isolation and identification of allelochemicals were aided by use of gas chromatography/mass spectroscopy. The results revealed the presence of three predominate chromatographic peaks: 7-epi-zingiberene [1], 9-hydroxy zingiberene [2] and 9-hydroxy,10,11-epoxy-zingiberene [3]. Results of testing isolated compounds for repellency to TSSM using bridge bioassays revealed that the repellent activities of [2] and [3] were each significantly higher than that for [1]. These results support the idea that the degree of repellency may differ among plant allelochemicals and also emphasize the potential value of introgressing the presence of [2] and [3] into cultivated tomato to enhance its arthropod resistance.